Masyarakat Bonokeling dalam Kajian Indigenous Counseling - Farikhatul Ubudiyah (Institut Agama Islam Negeri Curup, 2023)
This article aims to find out how the Bonokeling indigenous people of Pekuncen village, Jatilawang district, Banyumas district in the study of indigenous counseling. The theory used is about indigenous psychology which studies the unique behavior of indigenous people. The research methodology uses qualitative-exploratory. The results of this study describe the concept of indigenous counseling in the Muslim community of Bonokeling, that is: (a) kiai kunci being guide to anak putu who can be called non-professional counselors; (b) the principle of counseling is an equality of understanding between the kiai kunci and the anak-putu; (c) component of the counseling relationship based on genealogical principles; (d) have times in doing sowan; (e) has the principle of confidentiality between genealogy; and (f) there are stages of values taught by the kiai kunci to anak-putu.